2017
DOI: 10.1002/stc.1983
|View full text |Cite
|
Sign up to set email alerts
|

Control of underground blast induced building vibration by shape-memory-alloy rubber bearing (SMARB)

Abstract: Summary This paper focuses on the performance of shape‐memory‐alloy rubber bearings (SMARBs) compared to conventional lead‐plug or New‐Zealand (N‐Z) bearings in control of building vibration due to underground blast induced ground motion (BIGM). The performance is evaluated with regard to maximum acceleration and isolator displacement obtained by nonlinear time history analysis. In doing so the Bouc–Wen's model is used to represent the nonlinear behaviour of the N‐Z bearing and the superelastic behaviour of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For assessing the performance of the proposed active control scheme, a base‐isolated five‐story building structure described by Ramallo et al (based on a previous work by Kelly et al) is considered. This model has been intensively utilized by many researchers at the structural dynamics and control fields …”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For assessing the performance of the proposed active control scheme, a base‐isolated five‐story building structure described by Ramallo et al (based on a previous work by Kelly et al) is considered. This model has been intensively utilized by many researchers at the structural dynamics and control fields …”
Section: Simulation Resultsmentioning
confidence: 99%
“…This model has been intensively utilized by many researchers at the structural dynamics and control fields. 41,42 For this setup, the mass, stiffness, and damping matrices are given as in Equations 2-4, 23 where the masses, stiffness, and damping coefficients of each floor are detailed in Table 1. The Bouc-Wen parameters in Equations 5-6 that model the base isolator are given in Table 2.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, beam‐to‐column connections, base isolators, and bridges …”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, [14][15][16][17] beam-to-column connections, [18][19][20][21][22][23][24] base isolators, 25,26 and bridges. 27,28 Although the wire form of SMA has proven to be effective in providing energy dissipation and self-centring capability, there are still practical issues such as difficulty of gripping (especially when a large number of wires are to be included) and vulnerability to fracture at the gripping region due to local stress concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with electrorheological fluid, magnetorheological fluid (MRF), and shape memory alloy, shear thickening fluid (STF) is another smart material with excellent performance given that the characteristics of STF depend on its shear strain rate. Under high strain rate loading, the apparent viscosity of the contact interface changes dramatically, even from liquid phase to solid phase .…”
Section: Introductionmentioning
confidence: 99%